2020
DOI: 10.3389/fmicb.2020.570541
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Genetic Characterization of Classical Human Astrovirus Infection in Shanghai, 2015–2016

Abstract: Objective: Human astroviruses (HAstVs) are single-stranded RNA viruses of the Astroviridae family. Infection of classic HAstVs is one of the most common causes of acute viral gastroenteritis (infectious viral diarrhea). There is a lack of data on the prevalence and genetic characterization of classic HAstVs in acute viral gastroenteritis in the whole population. This study aimed to investigate the epidemiological trend, genotypes, viral co-infections, and viral loads of classic HAstVs in Shanghai, China, from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…Therefore, the infection of HAstV might be associated with the low environmental temperature, thus displayed a typical winter/spring seasonality. In addition, our results were also consistent with the results observed in Shanghai in 2015-2016, which also displayed a typical winter/spring seasonality ( 28 ). However, the infection peaks of HAstV varied in different years in this study, and the seasonality of HAstV infections in Chongqing needs to be further monitored.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the infection of HAstV might be associated with the low environmental temperature, thus displayed a typical winter/spring seasonality. In addition, our results were also consistent with the results observed in Shanghai in 2015-2016, which also displayed a typical winter/spring seasonality ( 28 ). However, the infection peaks of HAstV varied in different years in this study, and the seasonality of HAstV infections in Chongqing needs to be further monitored.…”
Section: Discussionsupporting
confidence: 91%
“…An increase in HAdV-F infections was observed during premonsoon and summer monsoon seasons between March to September in our study which concurs with reports from Thailand (Kumthip et al, 2019;Sugeçti et al, 2015). The dry, winter months during 2018-2020 in Kolkata also saw a peak in AstV infections similar to that observed in other countries like Shanghai, Nepal, Gabon (Lekana-Douki et al, 2015;Shrestha et al, 2021;Wu et al, 2020). NoV, otherwise known as 'winter vomiting bug' in most temperate countries such as Europe and North America (Ahmed et al, 2013), showed no definite seasonal pattern of infection in our study.…”
Section: Discussionsupporting
confidence: 86%
“…As no other genotypes have been reported in Shenzhen, it can be concluded that HAstV‐1 is the predominant astrovirus in the area. However, other genotypes such as HAstV‐2 and HAstV‐8 have been detected in other cities in China, 5 demonstrating the co‐circulation of multiple HAstVs. Therefore, it is crucial to enhance the surveillance of new strains and the frequency of various genotypes in Shenzhen.…”
Section: Discussionmentioning
confidence: 99%